Spontaneous Pneumomediastinum, Pneumoperitoneum, and Pneumoretroperitoneum After Endoscopic Cryoablation Without Frank Perforation. Issue 8 (14th August 2019) - Chen, Brendan; Ferreira, Jason
ABSTRACT: Perforation after endoscopic cryoablation is a rare but serious complication. We present a middle-aged male patient who presented for an elective session of endoscopic cryoablation for his Barrett esophagus with high-grade dysplasia. After cryoablation, the patient complained of abdominal pain, and his abdomen became distended and tympanic. Computed tomography showed pneumomediastinum, pneumoperitoneum, and pneumoretroperitoneum but no evidence of extraluminal contrast extravasation. The patient was treated with antibiotics and had no complications. To our knowledge, this is the first described case of pneumomediastinum, pneumoperitoneum, and pneumoretroperitoneum without frank perforation after endoscopic cryoablation.